NH‐NHI correlation in gigahertz‐peaked‐spectrum galaxies1. Issue 1 (February 2016) - Ostorero, L.; Morganti, R.; Diaferio, A.; Siemiginowska, A.; Stawarz, Ł.; Moderski, R.; Labiano, A.
Abstract: With the Westerbork Synthesis Radio Telescope, we performed HI observations of a sample of known X‐ray emitting Gigahertz‐peaked‐spectrum galaxies with compact‐symmetric‐object morphology (GPS/CSOs) that lacked an HI absorption detection. We combined radio and X‐ray data of the full sample of X‐ray emitting GPS/CSOs and found a significant, positive correlation between the column densities of the total and neutral hydrogen ( N H and N HI, respectively). Using a Bayesian approach, we simultaneously quantified the parameters of the N H ‐ N HI relation and the intrinsic spread of the data set. For a specific subset of our sample, we found N H ∝ N HI b, with b = 0.93 +0.49 –0.33, and ω int ( N H ) = 1.27 +1.30 –0.40 . The N H ‐ N HI correlation suggests a connection between the physical properties of the radio and X‐ray absorbing gas. (© 2016 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)